Effect of Digestate on growth and production of rice under rice – wheat cropping system - Pandey, Bisheshwor Prasad; Pant, Khem Raj; Yadav, Mathura; Khatri, Narayan (Journal of Agriculture and Natural Resources, 2019)
Field experiments were conducted during rainy seasons of 2017 and 2018 at National Wheat Research Program (NWRP), Bhairahawa to identify the suitable age and appropriate dose of digestate/biogas slurry regarding yield maximization of rice (cv. Ram dhan). The experiment compared the effect of different age [5 days (fresh), 90 days (3 months) and 180 days (6 months)] and dose (0, 5, 10 and 15 t ha-1) of digestate/biogas slurry on rice yield. The experiment was laid out in Randomized Complete Block design (RCBD) with three replications. Grain yield of rice was significantly higher (4.5 t ha-1) with the application of biogas slurry of 5 days than 90 days (4.3 t ha-1) age, in 2017 A. D. Similarly, yield was significantly higher (4.6 t ha-1) with the application of biogas slurry 5 days than of 90 days (4.5 t ha-1) age, in 2018.  Yield due to the application of biogas slurry of 5 days was equal to the yield resulted from the use of biogas slurry of 180 days in 2017 and 2018.  The pooled analysis showed that the yield with the application of biogas slurry of 5 days age was significantly higher (4.6 t ha-1) than the yield due to the application of biogas slurry of 90 (4. 4 t ha-1) and 180 days (4.5 t ha-1) age. The yield of rice has been found increasing significantly as the dose of biogas slurry was incremented from 0 t ha-1   to 15 t ha-1 in 2017, 2018 and in pooled analysis. The yield of rice was significantly higher (4.6 t ha-1)   in 2018 than in 2017 (4.4 t ha-1), in pooled analysis. Thus, the use of biogas slurry of the age of 5 days with the dose of 15 t ha-1 produced the  higher grain yield of rice.